Мастер и Маргарита: [роман : 16+ ] / Михаил Булгаков - Булгаков Михаил Афанасьевич (Pocketbook, 2014)
Экземпляры: СФ (20140411) / Инвентарный номер: 49767 / Цена: 90.30 / Сис.шифр: Р2 / Авт.знак: Б 90 / ГРНТИ: 17.82 / ББК: 84(2Рос.Рус)6